The Conflict Administration according to Dhamma - Thumkard, Phra Montree Tittaparakkamo (Wishing Journal Review, 2023)
The conflict administration must be had necessary dwell with Dhamma for all level education. Because of education was important basic for steady creative and nation development. In addition, we can create good education means people in nation must be quality too. So, school had been the most educate institute and then administrators also must have been important and good management too. Therefore, administrators must be managed and control school then must have been education management with efficiency. The way as school administrators have done by management control, so that administrators should have an efficiency good knowledge good skill good vision until support them to be good administrator and necessary in school as well as more efficient.